Diagnosis of urinary tract infection in infants under 3 months with fever without a source: reliability of urinalysis and urine culture - Benigno M. Méndez-Espinola; Emilio Gallardo-Aravena (Permanyer, 2023)
Background: Urinary tract infection (UTI) is infants' most common serious bacterial infection. This study aimed to investigate the reliability of urianalysis (UA) to predict UTI, to specify the colony forming units (CFU)/ml threshold for diagnosis, and to identify variables that help suspect bacteremia in infants under 3 months with UTI. Methods: We reviewed clinical records of children under 3 months hospitalized for a fever without source and recorded age, sex, days of fever pre-consultation, temperature and severity at admission, discharge diagnoses, laboratory tests, and treatments. According to the discharge diagnosis, we divided them into UTIs (-) and (+) with or without bacteremia. Results: A total of 467 infants were admitted: 334 with UTI and 133 without UTI. In UTIs (+), the pyuria had a sensitivity of 95.8% and bacteria (+) 88.3%; specificity was high, especially for nitrites (96.2%) and bacteria (+) (92.5%). Positive predictive value (PPV) for nitrites was 95.9%, for bacteria 96.7%, and oyuria 92.5%. Escherichia coli was present in 83.8% of urine and 87% of blood cultures. UTIs with bacteremia had inflammatory urinalysis, urine culture > 100,000 CFU/ml, and higher percentage of C reactive protein (CRP) > 50 mg (p= 0.002); 94.6% of the urine culture had > 50,000 CFU. Conclusions: The pyuria and bacteria (+) in urine obtained by catheterization predict UTI. The cut-off point for diagnosis was ≥ 50,000 CFU/ml. No variables to suspect bacteremia were identified in this study.